BRANDING IMAGE DAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DALAM PENGUATAN MUTU PENDIDIKAN ISLAM DI SMA KHADIJAH SURABAYA - Saeful Anam; Rohmatul Husnah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In providing education, schools must have quality as a manifestation that the school is quality. The quality of schools can be seen from various directions, one of which is the quality of Islamic education. the quality of Islamic education is urgent and can be done in two ways, the first is by using Branding image and Customer relationship management Branding image for madrasas is important because building a good image and reputation will grow benefits for scholl, including increasing customer trust and customer loyalty to choose scholl as an option for teaching and learning places. These two ways are the main thing to do as an effort to strengthen the quality of Islamic education.. This study aims to reveal about how: (1) the concept (2) process, , (3) out put, branding image andcustomer relationship management (CRM) as strengthening the quality of Islamic education in SMA Khadijah Surabaya This study uses a qualitative approach, descriptive type. Data collection techniques using observation, interviews, and documentation. The research instrument is the researcher himself. Data analysis used descriptive analysis method.